Женщины мира в 2015 году - United Nations Department of Economic; Social Affairs (United Nations, 2021)
This publication presents statistics and analysis on the status of women and men in the world, highlighting the current situation and changes over time. The report is the sixth in the series which has been published every five years, as called for in the Beijing Platform for Action adopted at the Fourth World Conference on Women in 1995. This edition emphasizes that progress towards the goal of gender equality has been made in the last two decades in most areas of concern, although uneven and at low pace. Through a life cycle approach, the publication reveals the challenges and opportunities faced by women during their different stages of life and based on where they reside. The different trajectories of women and men are highlighted in the statistical findings of the analysis undertaken in eight chapters of the report, each representing a broad area of concern: population and families, health, education, work, power and decision-making, violence against women, environment and poverty.